A novel mutation in CFAP47 causes male infertility due to multiple morphological abnormalities of the sperm flagella - Liu, Mohan; Dai, Siyu; Zhang, Jiying; Yang, Yihong; Shen, Ying; Liu, Hongqian; Yang, Yanting; Jiang, Chuan; Tian, Erpo (Frontiers in Endocrinology, 2023)
Abstract Introduction: A previous study suggested that loss of CFAP47 function is involved in multiple morphological abnormalities of the sperm ﬂagella (MMAF) in humans and mice. However, the comprehensive role of CFAP47 in spermatogenesis is largely unknown. Methods: Whole-exome sequencing (WES) was conducted to identify pathogenic variant in two patients with MMAF. The functional effect of the identified mutations was investigated by immunofluorescence staining and western blotting. Intracytoplasmic sperm injection (ICSI) was used to assist fertilization for the patient with MMAF. Results: In this study, we identified a novel missense mutation (c.1414G>A; p.V472M) in CFAP47 in two unrelated patients with oligoasthenoteratozoospermia. Intriguingly, in addition to the MMAF phenotype very analogous to the previous report, the two patients notably presented abnormal morphology of sperm heads, the sperm mitochondrial sheath was obviously disorganized, and the sperm annulus were almost defective. Further functional experiments confirmed that the expression of CFAP47 was markedly reduced in the spermatozoa of the patients. Mechanism analysis suggested that CFAP47 might regulate the expression of CFAP65, CFAP69 and SEPTIN4 through their physical interactions and thus modulating sperm morphogenesis. Conclusions: we revealed a novel mutation in CFAP47 and further expanded the phenotype and mutation spectrum of CFAP47, as well as the potential mechanism of CFAP47 manipulating spermatogenesis, finally providing important guidance for genetic counseling and targeted treatment for CFAP47 mutation-related male infertility.